Tertiary Autologous Breast Reconstruction After Implant-Based Reconstruction: Safety and Patient-Related Outcomes. (April 2023) - de Kerckhove, Maiko; Matsunaga, Noriko; Tomita, Shoichi; Fujii, Miwako; Terao, Yasunobu
Summary: Silicone breast implants are popularly used for breast reconstruction. As more patients receive long-term silicone breast implants, the number of replacement operations will also increase, and some patients prefer to change from silicone breast implantation to tertiary autologous reconstruction. We evaluated the safety of tertiary reconstruction and assessed patient views regarding the two reconstruction methods. We retrospectively analyzed patient backgrounds, surgical characteristics, and silicone breast implantation retention periods until tertiary reconstruction. We designed an original questionnaire to assess patient opinion regarding silicone breast implantation and tertiary reconstruction. Twenty-three patients (24 breasts) with decisive factors of patient-initiated elective surgery (n = 16), contralateral breast cancer occurrence (n = 5), or late-onset infection (n = 2) underwent tertiary reconstruction. The median time from silicone breast implantation to tertiary reconstruction was significantly shorter in patients with metachronous cancer (47 months) than that in those undergoing elective surgery (92 months). Complications included partial flap loss (n = 1), seroma (n = 6), hematoma (n = 5), and infection (n = 1). Total necrosis did not occur. Twenty-one patients responded to the questionnaire. The satisfaction score was significantly higher for abdominal flaps than for silicone breast implants. When presented with the option to select the initial reconstruction method again, 13 of 21 respondents chose silicone breast implantation. Tertiary reconstruction is beneficial because it reduces clinical symptoms and cosmetic complaints and is recommended as a bilateral reconstruction method, especially for patients with metachronous breast cancer. However, silicone breast implants, which are minimally invasive and associated with shorter hospital stays, were simultaneously found to be sufficiently attractive to patients.